2022
DOI: 10.1155/2022/3969542
|View full text |Cite
|
Sign up to set email alerts
|

Giant Parathyroid Adenoma-Associated Fracture, Not All Lytic Bone Lesions are Cancer: A Case-Based Review

Abstract: Introduction. Due to the early diagnosis of primary hyperparathyroidism the musculoskeletal manifestations of this disease are becoming less frequent. When this disease manifests secondary to a giant adenoma, it presents with more aggressive symptoms and can have important repercussions such as the hungry bone syndrome after parathyroidectomy. There are few reported cases of hyperparathyroidism secondary to a giant adenoma in the literature, as the presence of a brown tumor is often misinterpreted as a metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The authors reviewed data on 2 medical databases concerning giant PT adenomas starting with 2009, since first report was introduced, until 2021 and found 24 studies; HBS rate was reported in 25% of the cases with RHPT (USA), and in 4-87% of the participants diagnosed with PHPT. HBS was found to be correlated with larger tumors (such as giant PT adenomas), a PTH value above 1000 pg/mL, serum AP concentration of 3 times above normal upper limit, an increased number of osteoclasts at bone biopsy, the co-presence of skeleton complications such as brown tumors, and osteititis fibrosa cystica [7]. A similar case of a giant PT adenoma (of 5.6 cm largest diameter, and a weight of 28.7 g) was admitted for high calcium (of 13.7 mg/dL) and PTH (of 1240 pg/mL); the 66-year-old female associated a 4-week episode of HBS starting from the first day after PTx [51].…”
Section: Panel Of Investigations In Phpt and Rhptmentioning
confidence: 96%
See 4 more Smart Citations
“…The authors reviewed data on 2 medical databases concerning giant PT adenomas starting with 2009, since first report was introduced, until 2021 and found 24 studies; HBS rate was reported in 25% of the cases with RHPT (USA), and in 4-87% of the participants diagnosed with PHPT. HBS was found to be correlated with larger tumors (such as giant PT adenomas), a PTH value above 1000 pg/mL, serum AP concentration of 3 times above normal upper limit, an increased number of osteoclasts at bone biopsy, the co-presence of skeleton complications such as brown tumors, and osteititis fibrosa cystica [7]. A similar case of a giant PT adenoma (of 5.6 cm largest diameter, and a weight of 28.7 g) was admitted for high calcium (of 13.7 mg/dL) and PTH (of 1240 pg/mL); the 66-year-old female associated a 4-week episode of HBS starting from the first day after PTx [51].…”
Section: Panel Of Investigations In Phpt and Rhptmentioning
confidence: 96%
“…Giant PT adenomas (of more than 2-3 g) display a higher rate of bone complications in terms of brown tumors and osteitis fibrosa cystica which themselves are prone to post-PTX HBS, noting that usually the size of PT tumor associates with the levels of serum PTH [50]. Alvarez-Payares et al [7] added a new such case, a 55-year-old female with a giant PT adenoma (of 5 cm, and a weight of 16 g) who was post-operatory re-admitted for HBS (the symptoms started 72 h after surgery and the patient remained hospitalized for one month, also associating an aggravation of chondrocalcinosis and an acute episode of pulmonary embolism). The authors reviewed data on 2 medical databases concerning giant PT adenomas starting with 2009, since first report was introduced, until 2021 and found 24 studies; HBS rate was reported in 25% of the cases with RHPT (USA), and in 4-87% of the participants diagnosed with PHPT.…”
Section: Panel Of Investigations In Phpt and Rhptmentioning
confidence: 99%
See 3 more Smart Citations